Plantas e animais medicinais em assentamentos rurais do Baixo Munim, Maranhão - Silva, Lizandra Conceição Pimenta (2018)
Ethnobiology is an interdisciplinary field that study and interpret the traditional knowledge involving plants and animals. Ethnobotany and Ethnozoology are the sciences that study the interactions between humans and plants and animals species, respectively, mainly those native of the region where a given population lives. Traditional knowledge about the use of plants and animals for medicinal purposes is transmitted throughout the generations, but is at risk of disappearing in different regions due to the accelerated processes of ecosystem loss, fragmentation, rural exodus and urbanization. The objective of this research was to investigate medicinal practices that use native trees and animals carried out by traditional communities in rural settlements in the Baixo Munim region of Maranhão, Brazil. For this, local experts were identified through the "Snowball" method and semi-structured questionnaires and participatory observation were applied with them. Fifty-two people were interviewed, with women accounting for 83% of this public. All interviewees are farmers, and only 8% of them have completed the study cycle. A total of 42 native medicinal tree species were used in the communities from 18 of botanic families. The Fabaceae was the most representative (21.4%). The species with the highest frequency of citation were Bunchosia sp. and Himathanthus drasticus, both with 21 citations. In relation to the animals, 18 species and 17 families were used medicinally in humans. Mammal was the most representative taxonomic group (44.4%) and Boidae the most representative family (11.1%). The species with the highest frequency of citation was the snake Crotalus durissus (12). Among the interviewees, 88% transmit this knowledge to the new generations orally. The interviewees reported an expressive number of plants and animals for use in the medicinal preparation. Considering the risk of loosing this knowledge, it is essential to register these practices in traditional communities.